Rate of Depression, Anxiety and Stress among Interns/House Officers in Nigeria - Muhammad, Daha Garba; Gbonjubola, Yusuff Tunde; Jamiu, Monsur Olalekan; Abiodun, Adesola Oyinkansola (Journal of Health and Allied Sciences NU, 2024)
Background Medical school is one of the most academically and emotionally demanding programs. The mandatory house job and internship year adds to the already high level of stress associated with medical school. The amount of time and effort invested is considerable. This dedication could be harmful to the young trainees' health, causing worry, despair, and stress. This study was undertaken to determine the rate of anxiety, depression, and stress among interns and house officers in Nigeria.Materials and Methods This is a descriptive cross-sectional survey in which 138 participants were conveniently recruited. The study used a self-report questionnaire with two sections that took approximately 10 minutes to complete. The first section collected sociodemographic information of the participants and the Depression, Anxiety, and Stress Scale (DASS-21) was used in the second segment to assess depression, anxiety, and stress.Results The rate of depression, anxiety, and stress among the participants in this study is 37.3, 42.5, and 15.7%, respectively. In this study, only duration of training has significant association with depression and stress (p < 0.05). However, all other sociodemographic variables showed no significant association with depression, anxiety, and stress (p > 0.05).Conclusion The significantly high level of depression, anxiety, and stress found among the participants revealed that depression, anxiety, and stress are of public mental health concern. These may have negative effects on cognitive functioning, learning, and patient care.
Keywords: anxiety; depression; stress; intern; house officer